Loss of dorsomedial hypothalamic GLP-1 signaling reduces BAT thermogenesis and increases adiposity - Shin J. Lee; Graciela Sanchez-Watts; Jean-Philippe Krieger; Angelica Pignalosa; Puck N. Norell; Alyssa Cortella; Klaus G. Pettersen; Dubravka Vrdoljak; Matthew R. Hayes; Scott Kanoski; Wolfgang Langhans; Alan G. Watts (Elsevier, 2018)
Objective: Glucagon-like peptide-1 (GLP-1) neurons in the hindbrain densely innervate the dorsomedial hypothalamus (DMH), a nucleus strongly implicated in body weight regulation and the sympathetic control of brown adipose tissue (BAT) thermogenesis. Therefore, DMH GLP-1 receptors (GLP-1R) are well placed to regulate energy balance by controlling sympathetic outflow and BAT function. Methods: We investigate this possibility in adult male rats by using direct administration of GLP-1 (0.5 ug) into the DMH, knocking down DMH GLP-1R mRNA with viral-mediated RNA interference, and by examining the neurochemical phenotype of GLP-1R expressing cells in the DMH using in situ hybridization. Results: GLP-1 administered into the DMH increased BAT thermogenesis and hepatic triglyceride (TG) mobilization. On the other hand, Glp1r knockdown (KD) in the DMH increased body weight gain and adiposity, with a concomitant reduction in energy expenditure (EE), BAT temperature, and uncoupling protein 1 (UCP1) expression. Moreover, DMH Glp1r KD induced hepatic steatosis, increased plasma TG, and elevated liver specific de-novo lipogenesis, effects that collectively contributed to insulin resistance. Interestingly, DMH Glp1r KD increased neuropeptide Y (NPY) mRNA expression in the DMH. GLP-1R mRNA in the DMH, however, was found in GABAergic not NPY neurons, consistent with a GLP-1R-dependent inhibition of NPY neurons that is mediated by local GABAergic neurons. Finally, DMH Glp1r KD attenuated the anorexigenic effects of the GLP-1R agonist exendin-4, highlighting an important role of DMH GLP-1R signaling in GLP-1-based therapies. Conclusions: Collectively, our data show that DMH GLP-1R signaling plays a key role for BAT thermogenesis and adiposity. Keywords: Neuropeptide, Hypothalamus, Sympathetic nerve, Adipose tissue, Obesity